The importance of the epinephrine provocation test for the hidden type-1 congenital long QT syndrome - Adem Atici; Ramazan Asoğlu; Hasan Ali Barman; Irfan Sahin (KARE Publishing, 2020)
Congenital long QT syndrome (LQTS) is a genetic channelopathy associated with a high incidence of sudden cardiac death in children and young adults. QT interval prolongation is typically the primary finding on the electrocardiography (ECG) recordings, but a normal QT interval may be seen in as many as 40% of patients with LQTS due to incomplete penetrance. A normal QT interval on ECG in patients with LQTS is known as hidden LQTS. An epinephrine provocation test can help in the diagnosis of hidden LQTS. This case report describes the use of an epinephrine provocation test to diagnose hidden LQTS in 3 patients who had normal QT interval and corrected QT interval on ECG and a family history of sudden cardiac death.